ICT competencies, for Students and Teachers: dilemmas, paradoxes and perspectives - The French case - Baron, Georges-Louis (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2025)
This paper aims at briefly discussing issues linked with ICT representations and competencies. After briefly analyzing the case of informatics as a school subject in France. it considers the case of ICT competencies, for K-12 students, and teachers. Finally, it analyses some of the paradoxes of the new systems designed to assess these competencies.